MENGGOYANG AKAL, MENGGAPAI INTUISI Kajian Kritis atas Metode Koan dan Zazen di dalam Tradisi Zen - Reza A.A Wattimena (Institut Filsafat dan Teknologi Kreatif Ledalero, 2015)
Zen is a way of understanding our true self as human before any concept is produced by the thinking mind. This true self can be perceived, when we let go all of forms of concepts and abstractions, and move to the realm of intuition. In this sense, intuition is direct experience of reality without the mediation of any kind of concepts or abstractions. The Zen tradition offers two ways to help people achieve this state of mind, namely Zazen (sitting meditation) and Koan (interview with the Zen Master). The awareness of the true self, or intuition, can be seen also as the state of enlightenment. This is the true freedom. This paper examins Zazen and Koan practices in the Zen tradition critically, and looks at how both can contribute to the development of human life. Kata-kata kunci: Zazen, Koan, Zen, Jati Diri Sejati, Pencerahan Batin.